2006
DOI: 10.1161/01.atv.0000204334.48195.6a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced T-Cell Expression of RANK Ligand in Acute Coronary Syndrome

Abstract: Objective-Based on its role in inflammation and matrix degradation, we hypothesized a role for osteoprotegerin (OPG), RANK, and RANK ligand (RANKL) in coronary artery disease. Methods and Results-We examined the expression of various members of the OPG/RANKL/RANK axis in patients with stable and unstable angina and in the atherosclerotic lesions of apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mice. Our findings were: (1) Serum levels of OPG were raised in patients with unstable angina (nϭ40), but not in those with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
155
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(161 citation statements)
references
References 29 publications
3
155
1
2
Order By: Relevance
“…In bone, RANKL is expressed most abundantly in MSCs, osteoblasts and T cells [29] . Despite OPG being a known inhibitor of RANKL, its biological effect may depend on the molar ratio between RANKL and OPG [30] . In this study of ovariectomized rats, we demonstrated that although LF treatment seems to have an inhibitory effect on RANKL, it enhances OPG.…”
Section: Discussionmentioning
confidence: 99%
“…In bone, RANKL is expressed most abundantly in MSCs, osteoblasts and T cells [29] . Despite OPG being a known inhibitor of RANKL, its biological effect may depend on the molar ratio between RANKL and OPG [30] . In this study of ovariectomized rats, we demonstrated that although LF treatment seems to have an inhibitory effect on RANKL, it enhances OPG.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, by failing to neutralize RANKL, reduced OPG levels might favor cardiovascular disease, because RANKL overexpression is a prominent feature prone to rupture vulnerable atherosclerotic lesions, RANKL may also contribute to the transition from a stable to an unstable plaque (30), and the serum level of RANKL is a highly significant predictor of cardiovascular disease (31). However, it must be noted that neither serum RANKL levels nor the serum RANKL/OPG molar ratio were different in our PCOS patients compared with the non-hyperandrogenic Figure 1 Serum osteoprotegerin (OPG) and RANKL concentrations, and the serum RANKL/OPG molar ratio, in obese and nonobese PCOS patients (grey boxes) and non-hyperandrogenic controls (white boxes).…”
Section: Discussionmentioning
confidence: 99%
“…TNFa, OX40/OX40L and RANK/ RANKL) and inhibitory (e.g. TRAIL) effects on this process [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%